Effect of Covid and its Treatment Protocols on Chronic Generalized Periodontitis- A Prospective Study - S Hari Krishna Reddy; Chandrasekhar Reddy Madu; Hanusha Bathula; Chiranjeevi Vedula; Venugopal Kunthsam; K V S P. Gupta (Wolters Kluwer Medknow Publications, 2022)
Background: COVID-19 causes an inflammatory response that intensifies and can cause death. Periodontitis is also characterized by an inflammatory response elicited by microbial plaque, which intensifies and inflicts damage to the tissues. To address the effect of immunoinflammatory mechanisms, steroids were used extensively as a lifesaving drug and stayed as the mainstream drug in treating severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections. The present study aimed to investigate the possible impact of COVID-19 treatment protocols in chronic periodontitis patients. Materials and Methods: A total of 103 COVID-19-positive patients with a hospitalization period of at least 5 days with dental records were enrolled in the study. Based on Periodontal Index (PI) values, the subjects were categorized as having mild, moderate, and severe periodontitis. These patients, after undergoing treatment for COVID-19 were recalled after 6 months for periodontal status evaluation. Statistical analysis was made to test for any significant variation in the periodontal status before and after COVID-19 treatments. Results: The mean comparison of Periodontal Index (PI) values before and after COVID were 4.02 and 4.40, with a statistically significant (P ≤ 0.05). PI values of the patients on Dexamethasone pre and post COVID -b 19 were compared and found to be 3.86 and 4.83, respectively. Conclusion: The present study indicates that COVID-19 and its different treatment protocols were strongly associated with elevated periodontal disease worsening in COVID-19 survivors at 6-month follow-up.